Adverse effects of Croton urucurana B. exposure during rat pregnancy - Moraes-Souza, Rafaianne Queiroz; Soares, Thaigra Sousa; Carmo, Nágilla Orleanne Lima; Damasceno, Débora Cristina [UNESP]; Campos, Kleber Eduardo [UNESP]; Volpato, Gustavo Tadeu [UNESP] (Elsevier, 2017)
Ethnopharmacological relevance Croton urucurana presents several beneficial pharmacological properties. In Brazil, women who intend to interrupt the pregnancy indiscriminately use extracts of this plant as an abortifacient agent. Aim of study To evaluated the effect of aqueous extract of Croton urucurana latex on the maternal-fetal repercussions in rats. Methods Pregnant rats were randomly distributed into four experimental groups: Control=treated with water (vehicle); Treated 200=treated with a dose 200 mg/kg; Treated 400=dose 400 mg/kg and; and Treated 800=dose 800 mg/kg. The rats were orally treated by gavage with Croton urucurana or vehicle (water) during whole pregnancy. At term of pregnancy, all rats were killed to obtain maternal blood and tissues samples and fetal weight and anomaly analyses. Results C. urucurana treatment (Treated 400 and Treated 800) showed elevated liver enzymatic activities, reduced fetal body weight and placental efficiency. The Treated 800 group presented increased maternal total protein and cholesterol levels, and heart relative weight. All treated groups presented reduced maternal body weight and food intake, and increased pre-implantation loss rate compared to those of Control group. In addition, the treatment contributed to increased skeletal and visceral anomalies with higher doses. Conclusion Croton urucurana treatment caused maternal toxicity, which contributed for impairment embryo fetal development. These results showed that the indiscriminate use of plants during pregnancy should be avoided to prevent potential risk on maternal health as well as their offspring.
Keywords: Croton urucurana; Malformation; Plant; Pregnancy; Toxicity